Organising National Consortia for Licensing Bibliograhic, Citation and Fulltext Databases - Tollefsen, Sigrid; Gulliksen, Mimmi (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
RBT has been invited to present the status for consortia agreements for access to bibliographic databases, citation indexes and full-text resources in Norway.